Semi-structured Databases and the File System to Store and Manage XML Data - Afonso de Sousa, Artur (2002)
As new standards for technology specifications related to XML are unveiled, and stable tools to implement them become available, the widespread usage of XML as an universal format for data exchange between heterogeneous systems (using the Internet) will increasingly become a reality. Therefore, in order to deal efficiently with the large amounts of XML data that will be generated in the near future it is imperative to find efficient alternatives for the storage and management of this special kind of data. In this paper we analyze two possible approaches available for the storage and management of XML data (semi-structured databases and, of course, the file system). Furthermore, because we believe that the development of a standard for an XML query language will dramatically improve the usage of XML documents as an alternative means to store data, we conclude the paper with a brief reference, through examples, to some of the essential characteristics of the Xquery language.